Optical properties reconstruction using the adjoint method based on the radiative transfer equation. (January 2018) - Addoum, Ahmad; Farges, Olivier; Asllanaj, Fatmir
Highlights: We reconstruct the optical properties (µ a, µ s  and  g ) within a gradient-based algorithm. The gradient is efficiently computed by the RTE adjoint method. The simultaneous reconstruction of µ a and µ s is examined with crosstalk problem. The g factor is accurately reconstructed as a new optical contrast agent. The simultaneous reconstruction of µ s and g is achieved with reasonable accuracy. Abstract: An efficient algorithm is proposed to reconstruct the spatial distribution of optical properties in heterogeneous media like biological tissues. The light transport through such media is accurately described by the radiative transfer equation in the frequency-domain. The adjoint method is used to efficiently compute the objective function gradient with respect to optical parameters. Numerical tests show that the algorithm is accurate and robust to retrieve simultaneously the absorption µ a and scattering µ s coefficients for lowly and highly absorbing medium. Moreover, the simultaneous reconstruction of µ s and the anisotropy factor g of the Henyey–Greenstein phase function is achieved with a reasonable accuracy. The main novelty in this work is the reconstruction of g which might open the possibility to image this parameter in tissues as an additional contrast agent in optical tomography.